Simplify (x³)² × y⁵/y³: Step-by-Step Exponent Reduction

Question

Reduce the following equation:

(x3)2×y5y3= \frac{\left(x^3\right)^2\times y^5}{y^3}=

Video Solution

Solution Steps

00:00 Simplify
00:04 Let's take the multiplication out of the exponent
00:12 According to the laws of exponents, division of exponents with equal bases (A)
00:16 equals the same base (A) with the exponent difference (M-N)
00:20 We'll use this formula in our exercise
00:23 Let's equate term by term according to the formula and simplify
00:36 We'll keep the base and subtract between the exponents
00:56 According to the laws of exponents, any base (A) raised to power (M) raised to power (N)
00:59 equals the same base (A) raised to the product of the exponents (M*N)
01:04 We'll use this formula in our exercise
01:09 Let's equate term by term according to the formula and simplify
01:21 We'll keep the base and multiply between the exponents
01:37 And this is the solution to the question

Step-by-Step Solution

To solve the problem of reducing the expression (x3)2×y5y3\frac{\left(x^3\right)^2 \times y^5}{y^3}, we'll follow these steps:

  • Step 1: Simplify (x3)2\left(x^3\right)^2 using the power of a power rule.

  • Step 2: Simplify the expression using the division rule for y5y^5 divided by y3y^3.

Let's execute these steps:

Step 1: Apply the power of a power rule to (x3)2\left(x^3\right)^2.

According to the power of a power rule, (xm)n=xmn(x^m)^n = x^{m \cdot n}.

So, (x3)2=x32=x6\left(x^3\right)^2 = x^{3 \cdot 2} = x^6.

Step 2: Simplify the division of exponents for the yy variable.

The expression now looks like x6×y5y3\frac{x^6 \times y^5}{y^3}.

Using the division rule for exponents, ym/yn=ymny^m / y^n = y^{m-n}, we get:

y5/y3=y53=y2y^5 / y^3 = y^{5-3} = y^2.

Final Expression: Combining the results from Step 1 and Step 2, we obtain:

x6×y2x^6 \times y^2.

Therefore, the solution to the problem is x6×y2x^6 \times y^2.

Answer

x6×y2 x^6\times y^2